Nutritional Status and Causes of Anterior Cruciate Ligament Injury in Relation with Exercise Habit Among Patients of a Tertiary Care Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: ACL injuries, is a serious problem in sports. Treatment of ACL injury is costly and it often takes 12 months or more to return to sports or in worst case and lead to early retirement. The long term outcome is also concerning issue. Objective: The goal of this study was to identify the nutritional status and causes of injury in relation with exercise habit among the patients with anterior cruciate ligament injury.Methods: A cross-sectional descriptive study was carried out in a super specialty modern tertiary care level hospital in Dhaka, Bangladesh. Total 63 samples were collected purposively to conduct this study. Data were collected through face to face interview by pretested semi-structured questionnaire and anthropometry was measured by standard technique. Prior data collection written consent was taken from the respondents. Descriptive as well as inferential statistics were used for data analysis.Results: The mean age (±SD) of the respondents was 27.52 (±7.59) years where 95.3% were male patients and 4.7% were female patients. Regarding their nutritional status, 23.8%, 55.6% and 20.6% were normal, over weight and obese respectively. Moreover 61.9% respondents had regular exercise habit whereas 38.1% respondents had no regular exercise habit. Besides there was no significant association (p>0.05) found between causes of injury and types of injury with exercise habit.Conclusion: Most of the patients were over nourished and no significant association was found between vehicle used and causes of injury. Further large scale study is needed to get actual picture.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21026